Respuesta :

Answer:

x = -7

Step-by-step explanation:

Solve for x:

4 (1 - x) + 2 x = -3 (x + 1)

4 (1 - x) = 4 - 4 x:

2 x + 4 - 4 x = -3 (x + 1)

2 x - 4 x = -2 x:

-2 x + 4 = -3 (x + 1)

Expand out terms of the right hand side:

4 - 2 x = -3 x - 3

Add 3 x to both sides:

3 x - 2 x + 4 = (3 x - 3 x) - 3

3 x - 3 x = 0:

3 x - 2 x + 4 = -3

3 x - 2 x = x:

x + 4 = -3

Subtract 4 from both sides:

x + (4 - 4) = -4 - 3

4 - 4 = 0:

x = -4 - 3

-4 - 3 = -7:

Answer:  x = -7

Answer:

X=-7

Step-by-step explanation:

Ver imagen Аноним
ACCESS MORE